The Influence Of Work Enthusiasm And Work Motivation On Employees' Performance At Bank Bengkulu Branch Of Tais - Fitri, Dwi Kusmita; Irwanto, Tito (Utami Publisher, 2025)
This study aims to determine whether there is an effect of work enthusiasm and work motivation on employees’ performance at Bank Bengkulu Branch of Tais. This type of research is quantitative descriptive research, which is a technique used to explain and present numerical data through various statistical methods. The population in this study were all 27 employees of Bank Bengkulu Branch of Tais. While the sample is using the total sampling method of 27 people. Types and sources of data are primary and secondary data, while data collection techniques use questionnaires. The data analysis used in this research is simple linear regression test, t test and Determination (R2). The results of this study indicate that there is an influence of work enthusiasm and work motivation on employees’ performance at Bank Bengkulu Branch of Tais. The level of relationship between the two variables is in the very strong category, which means that the ability of the independent variable to explain the dependent variable is good.